Kepastian Hukum Lelang Eksekusi Objek Hak Tanggungan Berdasarkan Parate Executie - Rahmadi Indra Tektona; Moh. Ali; Anang Suindro (Universitas Katolik Widya Karya Malang, 2023)
In general, there are laws that provide protection to banks as lenders to obtain repayment of their debts when the debtor is in default, this is stated in Article 1131 of the Civil Code which reads: